Measuring the Efficiency of the Azerbaijan Banking System with Data Envelopment Analysis (2015-2019) - Baghirov, Alig; Rzayeva, Leyla (My University, 2022)
It is the duty of the Central Bank of the Azerbaijan Republic to apply monetary policy for the development of the banking system in the country. The Central Bank is responsible for the balanced and efficient use of banks' resources for the growth of the economy throughout Azerbaijan. In this study, the measurement of the efficiency of all 25 banks operating in Azerbaijan between 2015 - 2019 was investigated with constant return to scale, variable return to scale and Super efficiency models of an input-oriented Data Envelopment Analysis. According to the analysis results, efficient and inefficient banks were identified and compared, and potential improvement suggestions were developed for inefficient banks. With this, it was thought that the resources for the banking system could be used more efficiently. It has been recommended to the inefficient banks that they should increase their efficiency based on the effectiveness rates from the efficient banks such as Gunay Bank, Bank VTB, AFB Bank and Bank of Baku as reference. It is also recommended to reduce deposit costs in order to increase the volume of deposits to be received from customers. According to the findings, the efficiency of the banking system has increased over the years, and as a result, the average efficiency score of banks operating in Azerbaijan was 75 in 2015 and 95 in 2019. This research will be a source of resources for future researchers, banks, and bank employees and analysts.